The passions of Christ in high-medieval thought: an essay on christological development - Madigan, Kevin (Oxford studies in historical theology, 2007)
Introduction -- Humanity, divinity and biblical exegesis in early arian thought -- Christus proficiens? did christ progress in wisdom? -- Christus nesciens? was christ ignorant of the day of judgment? -- Christus patiens? did christ suffer pain in the passion? -- Christus passibilis? did christ experience fear and sorrow in gethsemane? -- Christus orans? : a praying god? -- Conclusion -- The passions of christ in ancient and medieval thought : continuities and discontinuities